A Review of the Rural Health Care System in Gujarat - Kumar, Jayant; Bhatia, Hitesh (Arthshastra Indian Journal of Economics & Research, 2014)
Health is not the mere absence of disease; it is a requisite for defining a person’s overall well being. Articles 39(e) (f), 42, and 47 in part IV of the Indian Constitution clearly define a state’s responsibility to guarantee a healthy life to the people of its country. The state’s obligation towards the health of its people is beyond social reasons. It is more because healthy people can only contribute productively towards nation building and high economic growth. It is expected that the state with high economic growth will be able to allocate more towards providing basic health facilities. A brief look into the status of health care facilities and public expenditure on health contradicts this assumption, especially in the case of the state of Gujarat. The present paper made a modest attempt to review selected aspects of the health care system in Gujarat. The subject matter of the study is confined to rural areas, and the study used only the secondary data available from various sources.